T112. PTSD AS A MEDIATOR OF THE RELATIONSHIP BETWEEN TRAUMA AND PSYCHOTIC EXPERIENCES. (18th May 2020) - Strelchuk, Daniela; Hammerton, Gemma; Croft, Jazz; Heron, Jon; Zammit, Stanley; Wiles, Nicola; Turner, Katrina
Abstract: Background: Trauma exposure is linked to the development of psychotic illnesses, but little is known about potentially modifiable mechanisms underlying this relationship. Despite the high prevalence of PTSD symptoms in psychotic illnesses, only a few studies have examined the role of PTSD as a mediator, and these were all cross-sectional. This study aims to examine whether PTSD symptoms mediate the relationship between trauma and psychotic experiences (PE), using data from a large birth cohort study. Methods: We used data from the Avon Longitudinal Study of Parents and Children (ALSPAC) to test whether: a) PTSD symptoms (at age 15) mediate the relationship between childhood trauma (age 0–14 years) and adolescent frequent or distressing psychotic experiences (age 12–18 years) (study of adolescent PE; n = 2, 952), and b) PTSD symptoms (reported at age 24 for traumatic event occurring before age 19) mediate the relationship between childhood/adolescent trauma (age 0–17 years) and incident frequent or distressing psychotic experiences in early adulthood (age 19–24 years) (study of adult PE; n = 2, 492). Associations between the variables of interest were examined with logistic regression, and mediation with the parametric g-computation formula. As sensitivity analyses, we i) examined broader and narrower psychotic outcomes, ii) included a measure of psychotic-like experiences at age 14 years as an intermediate confounder in the mediation model for adolescent psychotic experiences, and iii) repeated analyses using imputed data. Results: Exposure to trauma was associated with increased odds of psychotic experiences and PTSD symptoms both in adolescence and early adulthood (p<0.001). The association between PTSD and psychotic experiences was stronger in adolescence (p<0.001) than in adulthood (p=0.03). There was moderate evidence that PTSD symptoms mediated the relationship between childhood trauma and adolescent psychotic experiences (proportion mediated 14%), though evidence of mediation was much weaker for adult PE (proportion mediated 8%). In sensitivity analyses we observed similar results when using imputed data, and when modelling psychotic experiences at age 14 as an intermediate confounding for the adolescent PE outcome. The proportion mediated increased when examining more narrowly defined outcomes (19% for adolescent psychotic disorder). Discussion: These findings provide some evidence consistent with the thesis that psychotic experiences and disorder can occur consequent to PTSD symptoms after trauma exposure. Targeting PTSD symptoms might help prevent the occurrence of psychotic experiences and disorder in people with a trauma history.